Influence of android-based education on mothers’ knowledge in preventing uterine prolapse - Sarita, Sultina; Yustiari, Yustiari; Anwar, Khalidatul Khair; Syahrianti, Syahrianti (YCAB Publisher & IAKMI SULTRA, 2022)
Background: Pelvic organ prolapse is a common health problem and affects up to 40% of women who have given birth and are over 50 years old. Objective: This study aimed to determine the influence of android-based education on mothers’ knowledge in preventing uterine prolapse in the work area of the Poasia Primary Health care, Kendari City, Indonesia. Methods: This study used a quasi-experiment with one group pretest-posttest design. Data were collected from September to December 2019 among 60 mothers. In this study, the respondents were given education about preventing uterine prolapse in the form of PowerPoint (PPT) and videos using the android application. Descriptive statistics and the Wilcoxon test were used for data analysis. Results: Of 60 respondents, 52 respondents experienced an increase in knowledge after being given an education. There was a significant effect of education using PowerPoint (PPT) and videos in the android application on the improvement of mothers’ knowledge in preventing prolapse uteri (p = 0.000). Conclusion: There may be an influence of the android-based education in increasing mothers’ knowledge of preventing uterine prolapse. However, further study is needed to validate the findings.